MARKETING FUNCTIONS AND FARMER’S SHARE OF OIL PALM FRESH FRUIT BUNCH OF SELF-SUPPORT FARMERS IN BANYUASIN REGENCY SOUTH SUMATRA - Lifianthi, Lifianthi; Rosana, Elly; Thirtawati, Thirtawati (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
The marketing oil palm FFB is a process of the commodity flow accompanied by a transfer of ownership rights, creation of time utility, place utility, and form utility undertaken by marketing institutions that implement one or more marketing functions. Selling of oil palm FFB by the farmers involve village middlemen, and wholesaler. This type of marketing implementation seems to have an influence on FFB price at farmer’s gate. The results showed that marketing functions conducted by all marketing institutions were financing and risk-taking, while other marketing functions were done by individuals related to their position and requirement. The total marketing margin of the traders was IDR 700,00 (63.64% of FFB price at the farm gate), while the farmer’s share was 61.11% from the FFB price at the processing plant. There were two marketing channels of FFB in operation, the first included farmers – small traders – big traders – palm oil processing plant, and the second was farmers-big traders-palm oil processing plant. The second channel was more efficient, but the farmers prefer to use the first channel because their FFB production was not enough to fulfill the minimum selling required by the big traders. The majority of farmers still sell their FFB to village middlemen.